Teleworking in Peru - Arévalo Vela, Javier (2024)
The article addresses the rights and obligations of teleworking, and highlights the importance of personal service, subordination and confidentiality. It stresses the need to respect the working day and guarantee periods of digital disconnection, in line with the French legislation adopted by Peru. Health and safety in teleworking is emphasized, with obligations for the employer in risk prevention and accident investigation. In addition, it promotes the hiring of vulnerable populations in teleworking, providing them preference in the work modality, as long as they meet the requirements of the position. The objectives of the article include clarifying the responsibilities of teleworkers and employers, as well as promoting safe and equitable working conditions, including for vulnerable populations. It also seeks to highlight the benefits of telework for both employers and workers, such as reduced costs and expanded job opportunities. Likewise, a proposal is developed in order to promote teleworking in Peru. The present development allows us to conclude that telework is presented as a modern modality that alters some typical elements of the labor relationship, but keeps intact its essential components; it favors both employers and workers, by allowing cost reduction, higher productivity and access to job opportunities, while guaranteeing fundamental rights and safe working conditions; and it highlights the importance of promoting the labor inclusion of vulnerable populations, ensuring their access to telework under equal conditions.